PENGARUH GAYA KEPEMIMPINAN DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN BAGIAN NOSEW PADA PT ADIS DIMENSION FOOTWEAR - Novilia Lestari Fadriah; Eraera Hia; Temmy Setiawan (MANTRA (Jurnal Manajemen Strategis), 2026)
The Influence of Leadership Style and Workload on Employee Performance in the Nosew Department at PT Adis Dimension Footwear. This study examines the partial and simultaneous effects of leadership style and workload on employee performance. Using an associative quantitative method with 100 respondents, the results show that leadership style and workload have positive and significant effects on employee performance.